Pengaruh Independensi dan Profesionalisme Terhadap Kinerja Auditor Internal Dengan Budaya Organisasi sebagai Variabel Moderasi - Theresia Mentari; Gugus Irianto; Rosidi Rosidi (Jurnal Akuntansi dan Pajak, 2019)
This study aims to find empirical evidence related to impact of auditor’s independence and professionalism towards the internal auditor’s performance moderated by organizational culture. The sample of this study is internal auditors who work and has position as functional Officer Auditor and structural officers functions as an audit division in the provincial inspectorate located in the province of Central Kalimantan and chosen by random sampling technique with a total of 137 samples. The method of collecting data was survey through distribution directly. Data analysis was done out by using the Structural Equation Model - Partial Least Square (SEM-PLS) through SmartPLS version 3.0 software. The results of this study shows that independence of audtor and professionalism auditor has positive and significant impact on internal auditors performance. This study supports organizational culture as moderating variable, on impact auditors independence towards the internal auditor performance. This research support organizational culture as a moderating variable, on the impact of auditors professionalism impact towards the internal auditors performance.